Pengaruh Beban Kerja dan Budaya Organisasi Terhadap Loyalitas Karyawan Pada CV Asanka Wijaya - Saputra, Monika; Akmal, Samsul; Hidayat, Rahmat Al (STIA Bengkulu, 2024)
In this study, the researcher aimed to investigate the effect of workload and organizational culture on employee loyalty at CV Asanka Wijaya. This is a descriptive-causal study and a quantitative research. The survey method was used with non-random sampling technique, specifically purposive sampling, to select a sample of employees. Data were collected using a Likert-scale questionnaire and analyzed using regression analysis and descriptive statistics. The statistical analysis conducted in this study was a simple linear regression, preceded by tests for validity, reliability, and classical assumptions as preliminary tests. This study indicates that workload has a partial negative effect on employee loyalty. The effect of this variable is 0.501, or 50.1%. and that organizational culture has a positive influence on employee loyalty by 0.362, or by 36.2%..